A highly active crystal face co-exposed ternary flower-shaped Bi 0 / BiOI / ZCO absorbing material and preparation method and application thereof

Through the synergistic effect of ternary flower-like Bi0/BiOI/ZCO absorbing materials coexposed with high activity {110} and {001} crystal surfaces, the problem of removing PFOA pollution in environmental water bodies is solved, and carrier separation is significantly improved Efficiency and life span achieve efficient degradation of PFOA.

CN117983253BActive Publication Date: 2024-12-27LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410141088.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2024-12-27
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove perfluorooctanoic acid (PFOA) pollution in ambient water bodies, and the carrier separation efficiency and life of BiOI as a microwave absorbing material need to be improved.

Method used

Using ternary flower-like Bi0/BiOI/ZCO absorbing material coexposed by high activity {110} and {001} crystal planes, BiOI and ZnCo2O4 nanocubes were prepared by solvothermal method to form heterojunctions, and grown by hydrothermal method. Semi-metal Bi0 forms a highly active ternary composite material, and combines microwave radiation to carry out efficient defluorination of PFOA.

Benefits of technology

The ultra-high catalytic degradation activity of PFOA has been achieved, the microwave synergistic degradation capacity has been significantly improved, and the application of microwave catalytic technology in the field of water pollution purification of perfluoroalkyl compounds has been promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117983253B_ABST
    Figure CN117983253B_ABST
Patent Text Reader

Abstract

The present invention discloses a highly active crystal face co-exposed ternary flower-shaped Bi 0 / BiOI / ZCO absorbing material and preparation method and application. The present invention prepares 3D hierarchical BiOI microflowers with co-exposed {110} and {001} highly active crystal planes by a simple solvothermal method, and further hydrothermally binds them to ZnCo 2 O 4 The nanocubes form a BiOI / ZCO heterojunction, and the surface is hydrothermally grown again to grow 0D semi-metallic Bi in situ. 0 , and obtain highly active {110} and {001} co-exposed 3D hierarchical Bi 0 / BiOI / ZCO ternary composite MW absorption material. Driven by MW, the material exhibits ultra-high catalytic degradation activity for PFOA and has potential application prospects in the purification of environmental water bodies contaminated by perfluoroalkyl compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of wave absorbing materials, and particularly relates to a Bi- 0 / BiOI / ZCO absorbing material, preparation method and application in efficient defluorination and degradation of perfluorooctanoic acid. Background Art

[0002] Perfluorooctanoic acid (PFOA) is a typical perfluoroalkyl compound with extremely high thermal and chemical stability and surface activity. It is widely used in industrial products such as packaging materials, firefighting foams, lubricants, and coatings. PFOA can be absorbed by the human body through ingestion, inhalation, and skin contact, causing diseases such as cancer and liver enlargement. Its C-F bond has an extremely high bond dissociation energy, making its molecular structure stable and difficult to degrade naturally. PFOA that enters water bodies can threaten human life and health through the food chain. Therefore, it is urgent to find new methods to effectively remove PFOA contamination from environmental water bodies.

[0003] The catalytic technology of microwave (MW) synergistic absorbing materials has the advantages of low reaction activation energy, strong penetration, and fast reaction rate, and has been widely used in research on environmental pollution control. The core of this technology is to construct MW catalytic materials with high efficiency in MW absorption, rich active sites, and stable structure. The unique layered structure of BiOI is conducive to the efficient separation of carriers and the interlayer migration of target objects, making it a good MW absorbing material. Due to the anisotropy of different crystal faces of BiOI, its charge separation and aggregation properties can be controlled by regulating the degree of crystal face exposure. In order to further improve the carrier separation efficiency of the material and extend the carrier lifetime, constructing heterojunctions and Schottky junctions is a relatively effective approach. Summary of the Invention

[0004] In order to solve the above-mentioned technical problems, the present invention provides a ternary flower-shaped Bi with high active crystal face co-exposed and ultra-high carrier separation efficiency. 0 / BiOI / ZCO absorbing material, preparation method thereof and application in degrading PFOA.

[0005] The technical solution adopted by the present invention is: a highly active crystal face co-exposed ternary flower-shaped Bi 0 / BiOI / ZCO absorbing material is BiOI with {110} and {001} crystal planes co-exposed. 0 / BiOI / ZCO absorbing material; containing 10-25% Bi by mass 0 .

[0006] A highly active facet-co-exposed ternary flower-shaped Bi 0 A method for preparing a / BiOI / ZCO absorbing material, comprising the following steps:

[0007] 1) Preparation of ZCO: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were dissolved in ethanol, and the pH of the solution was adjusted to 9 with aqueous ammonia. The resulting suspension was transferred to a polytetrafluoroethylene-lined autoclave for hydrothermal reaction, washed and dried, and the resulting product was calcined in a muffle furnace to obtain ZCO;

[0008] 2) Preparation of BiOI / ZCO: Bi(NO3)3·5H2O was dissolved in anhydrous ethanol to obtain solution A, and KI was dissolved in deionized water to obtain solution B. Solution B was slowly added dropwise to solution A under vigorous stirring, and ZCO powder was then added. The resulting mixture was stirred for 2-3 hours and then transferred to an autoclave for hydrothermal reaction. The resulting product was washed and dried to obtain BiOI / ZCO.

[0009] 3)Bi 0 Preparation of BiOI / ZCO absorbing material: Bi(NO3)3·5H2O was dissolved in ethylene glycol, and then BiOI / ZCO was added. After ultrasonic dispersion, it was transferred to a reactor for hydrothermal reaction. The obtained product was washed and dried to obtain Bi 0 / BiOI / ZCO absorbing material.

[0010] Furthermore, in step 1), the hydrothermal reaction is carried out at 180° C. for 2 to 24 hours.

[0011] Furthermore, in step 1), the calcination is performed at 400° C. for 2 to 3 hours.

[0012] Furthermore, in step 2), the hydrothermal reaction is carried out at 180° C. for 2 to 24 hours.

[0013] Furthermore, in step 3), the hydrothermal reaction is carried out at 160° C. for 2 to 15 hours.

[0014] The highly active crystal surface provided by the present invention co-exposes the ternary flower-shaped Bi 0 Application of / BiOI / ZCO absorbing materials in synergistic microwave defluorination of perfluorooctanoic acid.

[0015] Further, the method is as follows: adjust the pH of the solution containing perfluorooctanoic acid to 2-5, add Bi 0 / BiOI / ZCO absorbing material, microwave irradiation for 1 to 6 minutes.

[0016] Furthermore, the microwave power is 700W.

[0017] Furthermore, the concentration of the solution containing perfluorooctanoic acid is 5 to 15 mg·L -1 ,Bi 0The added amount of / BiOI / ZCO absorbing material is 0.1-0.5 mg / mL.

[0018] The beneficial effects of the present invention are:

[0019] 1. The present invention prepares 3D hierarchical BiOI microflowers with co-exposed {110} and {001} highly active crystal faces by a simple solvothermal method, further hydrothermally binds them to form BiOI / ZCO heterojunctions with ZnCo2O4 nanocubes, and hydrothermally binds them again to form 0D semimetallic BiOI in situ on their surfaces. 0 , and obtain highly active 3D hierarchical Bi with co-exposed {110} and {001} planes 0 / BiOI / ZCO ternary composite MW absorbent material. Driven by MW, the material exhibits ultra-high catalytic degradation activity for PFOA.

[0020] 2. 3D hierarchical Bi with appropriate {110} and {001} active facet exposure ratio prepared by the present invention 0 The / BiOI / ZCO ternary composite MW absorption material exhibits stronger MW synergistic PFOA degradation ability, which helps promote the application of microwave catalysis technology in the field of perfluoroalkyl compound water pollution purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 1 is the XRD pattern of different samples prepared in Example 1.

[0022] Figure 2 It is BiOI-18(a,b), BiOI / ZCO-18(c,d), 20%Bi 0 SEM images of / BiOI / ZCO-18 (e, f). DETAILED DESCRIPTION

[0023] Example 1 Ternary Flower-Shaped Bi 0 Preparation of BiOI / ZCO Absorbing Materials (I) 0 Preparation of / BiOI / ZCO absorbing materials

[0024] 1. Preparation of ZnCo2O4 (ZCO) nanocubes:

[0025] 0.02 mol Co(NO3)2·6H2O and 0.01 mol Zn(NO3)2·6H2O were dissolved in 80 mL ethanol (75%), and the pH of the solution was adjusted to 9 with aqueous ammonia. The resulting suspension was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and maintained at 180°C for 20 h, washed and dried, and the resulting product was calcined in a muffle furnace at 400°C for 2 h to obtain ZnCo2O4 nanocubes, labeled as ZCO.

[0026] 2. Preparation of BiOI / ZCO:

[0027] Solution A was prepared by dissolving 0.9700 g of Bi(NO₃)₃·5H₂O in 20 mL of anhydrous ethanol. Solution B was prepared by dissolving 0.3320 g of KI in 20 mL of deionized water. Solution B was slowly added dropwise to solution A under vigorous stirring. Then, 0.0782 g of ZCO powder was dispersed into the solution. The mixture was stirred for 2 h and then transferred to an autoclave. The mixture was heated at 180°C for 18 h. The product was washed and dried to obtain BiOI / ZCO, which was labeled as BiOI / ZCO-18.

[0028] 3. Ternary Flower-Shaped Pencil 0 Preparation of / BiOI / ZCO absorbing materials:

[0029] 0.0970 g, 0.1455 g, 0.1940 g and 0.2425 g of Bi(NO3)3·5H2O were weighed and dissolved in 40 mL of ethylene glycol, and then 0.2570 g of BiOI / ZCO-18 obtained in step 2 was added, and after ultrasonic dispersion, the mixture was transferred to a 100 mL reactor and kept at 160 ° C for 12 h. The precipitates were washed and dried to obtain different Bi 0 Mass percentage of ternary flower-shaped Bi 0 / BiOI / ZCO absorber materials, marked as 10%Bi 0 / BiOI / ZCO-18 absorbing material, 15% Bi 0 / BiOI / ZCO-18 absorbing material, 20% Bi 0 / BiOI / ZCO-18 absorbing material and 25% Bi 0 / BiOI / ZCO-18 absorbing material.

[0030] (2) Comparative Example

[0031] Preparation of 3D flower-like BiOI: Solution A was prepared by dissolving 0.9700g of Bi(NO₃)₃·5H₂O in 20mL of anhydrous ethanol. Solution B was prepared by dissolving 0.3320g of KI in 20mL of deionized water. Solution B was slowly added dropwise to Solution A under vigorous stirring. The mixture was stirred for 2 hours and then transferred to an autoclave for reaction at 180°C for 2, 18, and 24 hours, respectively. After washing and drying, the resulting BiOI absorbers with exposed crystal faces were labeled BiOI-2, BiOI-18, and BiOI-24, respectively.

[0032] (3) Characterization

[0033] Figure 1From the XRD patterns of different samples prepared, it can be seen that several different BiOI have similar diffraction peak positions. The diffraction peaks at 2θ = 9.76°, 29.76°, 31.71°, 37.1°, 39.41°, 45.82°, 52.03° and 55.3° are attributed to (001), (102), (110), (103), (004), (104), (114) and (2 12) crystal plane (JCPDS10-0045), but there are significant differences in the relative intensities of the (110) and (001) peaks. The co-exposure degrees of the (110) and (001) crystal planes of BiOI-2, BiOI-18, and BiOI-24 are different. BiOI-2 exposes more (001) crystal planes, BiOI-24 exposes more (110) crystal planes, and BiOI-18 exposes both (001) and (110) crystal planes. All peaks of pure ZCO are consistent with its standard card (JCPDS No.23-1390). The characteristic peaks of BiOI can be clearly observed in the composite material BiOI / ZCO-18, proving that the loading of ZCO does not affect the crystal structure of BiOI. The weaker characteristic peak of ZCO (220) can be observed in BiOI / ZCO, mainly because the relative intensity of the pure ZCO peak is lower than that of BiOI, and the ZCO content in the composite material is low. Bi 0 In the / ZCO / BiOI-18 composite material, new diffraction peaks appeared at 2θ=27.16°, 37.94° and 39.61°, corresponding to the metal Bi 0 {012}, {104} and {110} planes (JCPDS No.44-1246), proving that Bi 0 Successful load.

[0034] Figure 2 It is BiOI-18(a,b), BiOI / ZCO-18(c,d), 20%Bi 0 SEM images of / BiOI / ZCO-18(e,f) Figure 2 In Figures a and b, it can be observed that BiOI-18 is a 3D flower-like structure assembled by stacking a large number of ultrathin nanosheets with a diameter of about 3-4 μm. Figure 2 In Figures c and d, it can be seen that ZCO nanoparticles are uniformly loaded on the surface of the BiOI three-dimensional petals. Figure 2 where e and f are 20% Bi 0 SEM image of / BiOI / ZCO-18, we can see Bi 0 Successfully and uniformly loaded on the surface of BiOI three-dimensional flowers.

[0035] Example 2Bi 0Application of / BiOI / ZCO absorbing materials in synergistic microwaves for efficient defluorination of perfluorooctanoic acid

[0036] Catalytic experiments are carried out in a laboratory-specific microwave instrument, whose temperature, power, and reaction time are controllable and equipped with a condensation reflux device.

[0037] (1) MW-driven Bi 0 Catalytic activity of / BiOI / ZCO

[0038] The method is as follows: measure 50mL of 10mg·L -1 PFOA standard solution (pH = 4.3) was placed in a 250 mL three-necked flask, and 15 mg of 20% Bi was added. 0 The microwave power was set at 700W for 5 minutes. Samples were taken to measure the content of the composite absorber. A comparative experiment was also conducted. The results are shown in Table 1.

[0039] Table 1 Comparison of PFOA removal effects within 5 min by different methods

[0040]

[0041] As shown in Table 1, the degradation effect of MW radiation alone on PFOA is almost negligible, and 20% Bi 0 / BiOI / ZCO-18 has a removal rate of only 9.2% for PFOA adsorption in 5 minutes. Under MW drive, the degradation efficiency of PFOA by BiOI-18 monomer is 19.9% ​​within 5 minutes, which is significantly higher than that of BiOI-2 and BiOI-24. The MW catalytic degradation effect of BiOI / ZCO-18 heterojunction on PFOA is further improved to 37.9%, and 20% BiOI-24 is significantly higher than that of BiOI-2 and BiOI-24. 0 The MW degradation efficiency of PFOA by / ZCO / BiOI-18 composite material can reach 97.7%, showing ultra-high MW-induced catalytic activity.

[0042] (2) Bi 0 Effect of / BiOI / ZCO dosage

[0043] The method is as follows: measure 50mL of 10mg L -1 PFOA standard solution (pH = 4.3) was placed in a 250 mL three-necked flask, and 5 mg, 10 mg, 15 mg, 20 mg and 25 mg of 20% Bi were added respectively. 0 The microwave power was set at 700 W for 5 minutes. Samples were taken to test the content of the ZCO-18 composite absorber. The results are shown in Table 2.

[0044] Table 2 Effect of catalyst dosage on PFOA degradation effect

[0045]

[0046] As can be seen from Table 2, as the amount of catalyst increases, the degradation efficiency also increases. When the catalyst dosage is 15 mg, the degradation rate can reach 97.7%. Further increase in the dosage does not significantly improve the catalytic efficiency.

[0047] (3) Influence of microwave radiation time

[0048] The method is as follows: measure 50mL of 10mg L -1 PFOA standard solution (pH = 4.3) was placed in a 250 mL three-necked flask, and 15 mg of 20% Bi was added. 0 The microwave irradiation power was set at 700W for 1-6 minutes. Samples were taken every 1 minute to test the content change. The results are shown in Table 3.

[0049] Table 3 Effect of MW irradiation time on PFOA degradation effect

[0050]

[0051] As can be seen from Table 3, as the MW time increases, the degradation efficiency also increases. After MW irradiation for 5 minutes, the degradation rate can reach 97.7%. Further extending the reaction time does not significantly improve the catalytic efficiency.

[0052] (4) Bi 0 Effect of load

[0053] The method is as follows: measure 50mL 10mg L -1 PFOA standard solution (pH = 4.3) was placed in a 250 mL three-necked flask, and 15 mg of 10% Bi 0 / BiOI / ZCO-18 absorbing material, 15% Bi 0 / BiOI / ZCO-18 absorbing material, 20% Bi 0 / BiOI / ZCO-18 absorbing material and 25% Bi 0 The microwave irradiation power was set at 700W for 5 minutes. Samples were taken to test the content of the absorbing material. The results are shown in Table 4.

[0054] Table 4 Different Bi 0 Effect of loading amount on PFOA degradation efficiency

[0055]

[0056] As can be seen from Table 4, under MW radiation, Bi 0The catalytic degradation effect of BiOI / ZCO-18 on PFOA 0 The increase of load showed a trend of increasing first and then decreasing. 0 The catalyst with a loading of 20% had the best degradation efficiency for PFOA within 5 minutes.

[0057] (V) Effect of different solution pH values ​​on PFOA degradation

[0058] The method is as follows: measure 50mL of 10mg L -1 The PFOA standard solution was placed in a 250 mL three-necked flask, and the pH of the solution was adjusted to 2, 4.3, 6, and 8, and 15 mg of 20% Bi was added. 0 The microwave power was set to 700W for 5 minutes. Samples were taken to test the content of the absorbing material. The results are shown in Table 5.

[0059] Table 5 Effect of different pH on PFOA degradation efficiency

[0060]

[0061] As shown in Table 5, as the pH decreases from 8 to 4.3, Bi 0 / ZCO / BiOI-18 increases the PFOA degradation efficiency, and the catalytic activity is optimal at pH 4.3. Further decreasing the pH to 2 decreases the catalytic activity.

Claims

1. A highly active crystal face co-exposed ternary flower-shaped Bi 0 / BiOI / ZCO absorbing material, characterized in that: The highly active crystal surface co-exposes the ternary flower-shaped Bi 0 / BiOI / ZCO absorber is BiOI with {110} and {001} planes co-exposed. 0 / BiOI / ZCO absorbing materials; According to the mass percentage, it contains 10-25% Bi 0 ; The highly active crystal face co-exposes the ternary flower-shaped Bi 0 The preparation method of the / BiOI / ZCO absorbing material comprises the following steps: 1) Preparation of ZCO: Co(NO3)2·6H2O and Zn(NO3)2·6H2O were dissolved in ethanol, the pH value of the solution was adjusted to 9 with aqueous ammonia, the resulting suspension was transferred to a polytetrafluoroethylene-lined autoclave for hydrothermal reaction, washed and dried, and the resulting product was calcined in a muffle furnace to obtain ZCO; 2) Preparation of BiOI / ZCO: Dissolve Bi(NO3)3·5H2O in anhydrous ethanol to obtain solution A, and dissolve KI in deionized water to obtain solution B. Under vigorous stirring, slowly add solution B dropwise to solution A, and then add ZCO powder. After stirring the resulting mixture for 2 to 3 h, transfer it to an autoclave for hydrothermal reaction. The obtained product is washed and dried to obtain BiOI / ZCO. 3) Bi 0 Preparation of BiOI / ZCO absorbing material: Dissolve Bi(NO3)3·5H2O in ethylene glycol, add BiOI / ZCO, disperse evenly by ultrasonication, transfer to a reactor, perform hydrothermal reaction, wash and dry the obtained product, and obtain Bi 0 / BiOI / ZCO absorbing material.

2. A highly active crystal face co-exposed ternary flower-shaped Bi according to claim 1 0 / BiOI / ZCO absorbing material, characterized in that: In step 1), the hydrothermal reaction is carried out at 180°C for 2 to 24 hours.

3. A highly active crystal face co-exposed ternary flower-shaped Bi according to claim 1 0 / BiOI / ZCO absorbing material, characterized in that: In step 1), the calcination is performed at 400° C. for 2 to 3 h.

4. A highly active crystal face co-exposed ternary flower-shaped Bi according to claim 1 0 / BiOI / ZCO absorbing material, characterized in that: In step 2), the hydrothermal reaction is carried out at 180°C for 2 to 24 hours.

5. A highly active crystal face co-exposed ternary flower-shaped Bi according to claim 1 0 / BiOI / ZCO absorbing material, characterized in that: In step 3), the hydrothermal reaction is carried out at 160° C. for 2 to 15 hours.

6. The highly active crystal face co-exposed ternary flower-shaped Bi according to claim 1 0 Application of / BiOI / ZCO absorbing materials in synergistic microwave for efficient defluorination degradation of perfluorooctanoic acid.

7. The use according to claim 6, characterized in that The method is as follows: adjust the pH of the solution containing perfluorooctanoic acid to 2-5, add Bi 0 / BiOI / ZCO absorbing material, microwave irradiation for 1 to 6 min.

8. The use according to claim 7, characterized in that The microwave power was 700 W.

9. The use according to claim 7, characterized in that: The concentration of the solution containing PFOA is 5-15 mg·L -1 ,Bi 0 The added amount of / BiOI / ZCO absorbing material is 0.1-0.5 mg / mL.